(untitled) - Martina Smrekar; Sanja Ledinski Fičko; Biljana Kurtović; Boris Ilić; Snježana Čukljek; Martin Tomac; Ana Marija Hošnjak (University of Ostrava, 2022)
Aim: The aim of the study was to translate the Satisfaction with Simulation Experience (SSE) scale in Croatian language and examine whether the SSE scale was valid and reliable among Croatian nursing students. Design: In May 2020, a cross-sectional study was conducted at the University of Applied Health Sciences in Croatia. A 145 bachelor's degree nursing students participated in the study. Methods: To determine the instrument's internal consistency reliability, the Cronbach alpha coefficient was used. In addition, Confirmatory factor analysis, Bartlett's sphericity test, the Kaiser-Olkin statistic and Kolmogorov-Smirnov tests were used. Results: Cronbach's alpha coefficient demonstrated a high consistency of the Croatian version of SSE scale (α = 0.92). The Kaiser-Meyer-Olkin (KMO = 0.895) and the Bartlett's sphericity (p < 0.000) demonstrate significant results. The confirmatory factor analysis CFA has yielded a three-factor structure of SSE scale. Conclusion: The Croatian version of Satisfaction with Simulation Experience scale (CRO - SSE) has shown adequate psychometric properties making it a suitable tool for examining the satisfaction of nursing students with the simulation experience in Croatian context.